Assessment of dose contribution to pelvic lymph nodes in patients undergoing brachytherapy for carcinoma cervix - Deepak Sharma; Amrut S Kadam; Ramashish Kumar; Raghavendra BK; Srihari G; Perpetua Shruthi A; Varun Chandra (Asian Journal of Medical Sciences)
Background: The inclusion of pelvic lymph node (PLN) metastasis in the FIGO staging system has impacted disease classification and patient survival. Brachytherapy is a key component in managing carcinoma cervix; however, the dose contribution of brachytherapy to PLNs remains unclear.